Outcome of staged excision with pathologic margin control in high-risk basal cell carcinoma of the head region, - Reza Kavoussi; Hossein Kavoussi; Ali Ebrahimi; Nader Salari; Seyed Hamid Madani (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: High-risk basal cell carcinoma involves a significant rate of basal cell carcinoma that requires Mohs micrographic surgery for definitive treatment. Staged excision with pathologic margin control is a simple, accessible, and curative procedure suggested for the treatment of high-risk basal cell carcinoma. Objective: To evaluate the results of staged excision of high-risk basal cell carcinoma in the head region. Methods: This interventional study was performed on patients with high-risk basal cell carcinoma, who underwent staged excision until the margins were free of tumor. Results: A total of 122 patients (47 females and 75 males) with mean age of 57.66 ± 9.13 years were recruited in this study. Nasal and nodular types were the most common of both clinical and pathologic forms, respectively. Further, 89.3 % of cases were cured by staged excision after four years of follow-up. There was a significant relationship between treatment outcomes and recurrent lesions, multiplicity of risk factors, long-standing disease, and pathologic type. There was also a significant association between the number of surgical excisions and multiplicity of risk factors, as well as recurrence, location, and size of basal cell carcinoma. Study limitations: Lack of magnetic resonance imaging assessment in cases of suspected perineural invasion. Conclusions: High-risk basal cell carcinoma had a high cure rate by staged excision. Patients with more risk factors and those with nasal and recurrent basal cell carcinoma required more staged excisions. Failure of treatment is more probable in patients with more risk factors, long-standing lesions, and high-risk pathologic and recurrent basal cell carcinomas.